The genetics in substance use disorder: a review - Yüncü, Zeki; Savaş, Haluk A. (Journal of Dependence, 2007)
It was thought earlier that environmental and social conditions were effective in the progress of substance use disorder but upon the developments in the genetics area it came forward that the genetic reasons play an important role.The substance use disorder is a complicated process. This process starts with trying the substance, continues with constant use and results in addictiveness progress. The impact of genetic mechanisms on the different levels of this process should be enlightened.It is notified that the addictiveness of alcohol, cigarette, heroin and cocaine pass through the family. The genetic of alcohol use disorder has been studied more compared to the substance use disorder’s. As a result of these studies it was stated that the genetic impact in alcohol use disorder is more compared to the others.A genetic settlement that is agreed in the substance use disorder progress has not been obtained yet. The reason for this is that the formation of this sickness is attributed to the polygenic reasons. This situation causes the sickness to come in front of us with very different phenotypical features. The exposure of these different phenotypical features will guide the study of genetic ground
Keywords: Substance use disorder; genetics; adolescent